GLAMPING PADA OBJEK WISATA ALAM DI PANTAI NATEH MERATUS, KABUPATEN HULU SUNGAI TENGAH - Hidayah, Nurul; Hartono, Rudi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2024)
Indonesia is a country consisting of islands, one of which is Kalimantan which is rich in tourist attractions including natural tourism. South Kalimantan emphasizes its river tourism sector, including natural river tourist attractions. One of these tourist attractions is Nateh Meratus Beach, in Nateh village, Hulu Sungai Tengah Regency. It is necessary to develop attractions as well as efforts to maintain and maintain natural conditions as the main tourist attraction. Fulfillment of accommodation facilities is part of the development. An interesting accommodation that has the concept of being close to nature, namely Glamorous Camping (Glamping). Glamping accommodation design needs to consider ecological aspects. Ecological architecture is a method for linking these problems and then providing architectural solutions.